2003
DOI: 10.1207/s15327027hc1504_06
|View full text |Cite
|
Sign up to set email alerts
|

Are Social Norms Campaigns Really Magic Bullets? Assessing the Effects of Students' Misperceptions on Drinking Behavior

Abstract: In an attempt to curb excessive drinking on college campuses, many universities have turned to "social norms" marketing campaigns. Despite widespread acceptance among health educators, empirical results are clouded by measurement problems. This study, based on a random sample of 550 students, examined the effects of misperceptions of friends' and typical college students' drinking on one's drinking behavior. Results indicate that drinking behavior is positively related to perceptions of friends' drinking as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 36 publications
10
72
2
2
Order By: Relevance
“…The lack of significant differences between the degree of misperceptions of men and women is in contrast to previous research, which has found women to have an overall greater degree of misperception than men (e.g., Campo et al, 2003;Korcuska and Thombs, 2003). There are several possible explanations for this.…”
Section: Discussioncontrasting
confidence: 77%
“…The lack of significant differences between the degree of misperceptions of men and women is in contrast to previous research, which has found women to have an overall greater degree of misperception than men (e.g., Campo et al, 2003;Korcuska and Thombs, 2003). There are several possible explanations for this.…”
Section: Discussioncontrasting
confidence: 77%
“…An important and significant body of research uses surveys to elicit ethical norms from individuals, groups or organizations (see for example Schwartz, 1973;Victor and Cullen 1988;Cullen and Bronson 1993;Perkins and Wechsler 1996;Kanazawa and Stil 2001;Campo et al, 2003, Perkins and Wechsler, 1996, Schwartz, 1973, Jones and Kavanagh 1996. 6 While the strength of using a survey is that it can be adapted to ask about norms in different settings for different situations, and do so in a cost-effective manner, this format is not incentive compatible with the revelation of true beliefs or preferences by respondents (Furnham 1986;Friedman and Sunder 1995;Patel 2003;Dunn and Schome 2009;Auger and Devinney 2007;DeJong et al 2010).…”
Section: Related and Existing Workmentioning
confidence: 99%
“…Foss et al 2003). Studies have also been criticised on measurement issues (Campo et al 2003). Previous social norms campaigns have often included additional components (Borsari and Carey 2000;Walters 2000).…”
Section: Criticisms Of the Social Norms Approachmentioning
confidence: 99%